CULTIVATION AND INGESTIBILITY OF ANGOLE PEAS (CAJANUS CAJAN) IN SAHEL GOAT IN NIGER - Saidou, Ousseina; M. Mouctari, Ousseini Mahaman; Barhiré, Ridouane Ibrahim; Guimbo, Iro Dan (International Journal of Research -GRANTHAALAYAH, 2019)
This study was conducted on the experimental site of the Faculty of Agriculture of Abdou Moumouni University of Niamey. Objective of the work is to study the culture of species Cajanus cajan while determining its applicability to the Sahel goat. Germination test was carried out in petri dishes. Experimental set-up consists of 360 pockets distributed in three blocks each containing four plots of which three plots received urea, three received the NPK, three others received the manure and in the end three were kept as controls. Time between the establishment of grain culture in petri dishes and first appearance of radicle is one day and the staggering of germination is four days. The emergence of seedlings was observed 7 days after sowing in pockets. The seeds have a germination rate of 67.14%. At the first harvest, biomass production is 78.84; 89.42 and 79.87kg / ha respectively for plants treated with urea, NPK 15-15-15 and for plants treated with manure. Production of control plants is 50.45 kg / ha. Species Cajanus cajan has a higher appetence rate (80%) compared to species Leuceuna lecocephala and Gliricidia sepium which have respectively 66.66 and 46.66%.